Comparative Physiological and Molecular Analyses of Two Contrasting Flue-Cured Tobacco Genotypes under Progressive Drought Stress - Su, Xinhong; Wei, Fengjie; Huo, Yongjin; Xia, Zongliang (Frontiers in Plant Science, 2017)
Drought is a major environmental factor that limits crop growth and productivity. Flue-cured tobacco (Nicotiana tabacum) is one of the most important commercial crops worldwide and its productivity is vulnerable to drought. However, comparative analyses of physiological, biochemical and gene expression changes in flue-cured tobacco varieties differing in drought tolerance under long-term drought stress are scarce. In this study, drought stress responses of two flue-cured tobacco varieties, LJ851 and JX6007, were comparatively studied at the physiological and transcriptional levels. After exposing to progressive drought stress, the drought-tolerant LJ851 showed less growth inhibition and chlorophyll reduction than the drought-sensitive JX6007. Moreover, higher antioxidant enzyme activities and lower levels of H2O2, Malondialdehyde (MDA), and electrolyte leakage after drought stress were found in LJ851 when compared with JX6007. Further analysis showed that LJ851 plants had much less reductions than the JX6007 in the net photosynthesis rate and stomatal conductance during drought stress; indicating that LJ851 had better photosynthetic performance than JX6007 during drought. In addition, transcriptional expression analysis revealed that LJ851 exhibited significantly increased transcripts of several categories of drought-responsive genes in leaves and roots under drought conditions. Together, these results indicated that LJ851 was more drought-tolerant than JX6007 as evidenced by better photosynthetic performance, more powerful antioxidant system, and higher expression of stress defense genes during drought stress. This study will be valuable for the development of novel flue-cured tobacco varieties with improved drought tolerance by exploitation of natural genetic variations in the future.